Technical Considerations in Decompressive Craniectomy in the Treatment of Traumatic Brain Injury - Huang, X. (Ivyspring International Publisher, 2010)
Refractory intracranial hypertension is a leading cause of poor neurological outcomes in patients with severe traumatic brain injury. Decompressive craniectomy has been used in the management of refractory intracranial hypertension for about a century, and is presently one of the most important methods for its control. However, there is still a lack of conclusive evidence for its efficacy in terms of patient outcome. In this article, we focus on the technical aspects of decompressive craniectomy and review different methods for this procedure. Moreover, we review technical improvements in large decompressive craniectomy, which is currently recommended by most authors and is aimed at increasing the decompressive effect, avoiding surgical complications, and facilitating subsequent management. At present, in the absence of prospective randomized controlled trials to prove the role of decompressive craniectomy in the treatment of traumatic brain injury, these technical improvements are valuable.